Lone wolf - Palmer, Diana; Pearce, Kate, 1963-; Zanetti, Rebecca (Zebra Books, Kensington Publishing Corp., 2021)
Three celebrated New York Times best-selling authors team up in this collection of novellas that celebrates the loyalty and nobility of the wolf and includes Diana Palmer's “Colorado Cowboy,” in which a wildlife rehabilitator falls in love with a woman on the run.